1997
DOI: 10.1074/jbc.272.8.5128
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation by Peroxisome Proliferator-activated Receptor γ Is Inhibited by Phosphorylation at a Consensus Mitogen-activated Protein Kinase Site

Abstract: The nuclear receptor peroxisome proliferator-activated receptor ␥ (PPAR␥) regulates transcription in response to prostanoid and thiazolidinedione ligands and promotes adipocyte differentiation. The amino-terminal A/B domain of this receptor contains a consensus mitogen-activated protein kinase site in a region common to PPAR␥1 and -␥2 isoforms. The A/B domain of human PPAR␥1 was phosphorylated in vivo, and this was abolished either by mutation of serine 84 to alanine (S84A) or coexpression of a phosphoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
405
3
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(442 citation statements)
references
References 43 publications
24
405
3
4
Order By: Relevance
“…It is known that PyMT activates the ras pathway that stimulates mitogen-activated protein (MAP) kinase (58). Several studies have shown that MAP kinase directly phosphorylates PPAR␥, and the phosphorylated PPAR␥ has greatly reduced transcriptional activity and ability to promote cell differentiation (43,59,60). A combined effect of the MAP kinase activation by PyMT and AIB3 haplodeficiency on the reduction of PPAR␥ transcriptional activity may additively alter the function of PPAR␥ on cell differentiation and promote PyMT-induced mammary tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PyMT activates the ras pathway that stimulates mitogen-activated protein (MAP) kinase (58). Several studies have shown that MAP kinase directly phosphorylates PPAR␥, and the phosphorylated PPAR␥ has greatly reduced transcriptional activity and ability to promote cell differentiation (43,59,60). A combined effect of the MAP kinase activation by PyMT and AIB3 haplodeficiency on the reduction of PPAR␥ transcriptional activity may additively alter the function of PPAR␥ on cell differentiation and promote PyMT-induced mammary tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of PPAR 2 at serine residue 112 within the AF1 domain by growth factor (extra-cellular signal-regulated kinases 1/2) or stress-induced (p38/Jun NH 2 -terminal kinase 1/2) kinases represses PPAR transcriptional activity [34]. Indeed, over-expression of a phosphorylation defective PPAR mutant (in which serine 112 is mutated to alanine [PPAR S112A]) in mouse NIH-3T3 fibroblasts or 3T3-L1 pre-adipocytes results in enhanced adipogenesis compared with wild-type protein [12,35]. In vivo, homozygous PPAR S112A knock-in mice are protected from high-fat diet-induced insulin resistance and display decreased adipocyte size, elevated serum adiponectin, and reduced FFA levels [36].…”
Section: Page 7 Of 25mentioning
confidence: 99%
“…24 However, the increased adiposity was postulated to have resulted from a gain-of-function, with increased receptor transactivation due to P115Q, inferred because phosphorylation of Ser114 reduced the ability of the receptor to mediate adipocyte differentiation and lipid accumulation. 25,26 Heterozygosity for either PPARg V290M or P467L was initially reported in nonlipodystrophic subjects with severe insulin resistance. 27 However, later re-evaluation of subjects with PPARg V290M or P467L showed loss of subcutaneous limb fat and atrophy of buttock fat, confirming that mutant PPARg causes lipodystrophy.…”
Section: Pparc Mutations In Partial Lipodystrophy (Fpld3)mentioning
confidence: 99%